Reflection on Background Knowledge Implementation Using Top-down Activities - Fitri Hidayati; Basikin Basikin (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2018)
This paper attempts to examine students’ reaction and potential challenges encountered in the implementation of activities which stimulate their background knowledge. The authors implemented lesson plan which used top-down activities to raise students’ awareness of the use of background knowledge. The analysis in this reflection paper used two evaluation questions. The result showed that there are several reactions from the students as well as problems arose during the implementation of the activities. The reactions and problems are varied determined by the type of the exercise. Additionally, more explanations and examples are needed to be supplied before and also during the activity of completing the exercises. Those are necessary because during the activities, some students seemed to hesitate and needed more encouragement. Finally, continue practice using these type of exercises might give positive result in improving students’ awareness of background knowledge in discourse.